Oligomer-Targeting Prevention of Neurodegenerative Dementia by Intranasal Rifampicin and Resveratrol Combination – A Preclinical Study in Model Mice - Umeda, Tomohiro; Sakai, Ayumi; Shigemori, Keiko; Yokota, Ayumi; Kumagai, Toru; Tomiyama, Takami (Frontiers in Neuroscience, 2021)
Amyloidogenic protein oligomers are thought to play an important role in the pathogenesis of neurodegenerative dementia, including Alzheimer’s disease, frontotemporal dementia, and dementia with Lewy bodies. Previously we demonstrated that oral or intranasal rifampicin improved the cognition of APP-, tau-, and α-synuclein-transgenic mice by reducing the amount of Aβ, tau, and α-synuclein oligomers in the brain. In the present study, to explore more effective and safer medications for dementia, we tested the drug combination of rifampicin and resveratrol, which is a multifunctional natural polyphenol with the potential to antagonize the adverse effects of rifampicin. The mixture was intranasally administered to APP-, tau-, and α-synuclein-transgenic mice, and their memory and oligomer-related pathologies were evaluated. Compared with rifampicin and resveratrol alone, the combinatorial medicine significantly improved mouse cognition, reduced amyloid oligomer accumulation, and recovered synaptophysin levels in the hippocampus. The plasma levels of liver enzymes, which reflect hepatic injury and normally increase by rifampicin treatment, remained normal by the combination treatment. Notably, resveratrol alone and the combinatorial medicine, but not rifampicin alone, enhanced the levels of brain-derived neurotrophic factor (BDNF) and its precursor, pro-BDNF, in the hippocampus. Furthermore, the combination showed a synergistic effect in ameliorating mouse cognition. These results show the advantages of this combinatorial medicine with regards to safety and effectiveness over single-drug rifampicin. Our findings may provide a feasible means for the prevention of neurodegenerative dementia that targets toxic oligomers.